KEWENANGAN PENYELIDIKAN, PENYIDIKAN DAN PENUNTUTAN DALAM SISTEM PENEGAKAN HUKUM INDONESIA - Armunanto Hutahaean (Fakultas Hukum Universitas Kristen Indonesia, 2026)
The judicial system is essentially synonymous with the system of law enforcement, as judicial proceedings fundamentally constitute a process through which the law is upheld.Effective law enforcement, however, requires more than a coherent and comprehensive body of legislation; it also depends on institutional actors that serve as the primary instruments of legal implementation. These law enforcement institutions operate within an integrated framework that collectively forms the Criminal Justice System. Within this framework , law enforcement authorities inevitably function as the principal actors responsible for operationalizing and safeguarding legal norms. Law cannot enforce itself, nor can it realize the normative intentions embedded in statutory provisions without the active involvement of law enforcement authorities.The law enforcement process typically begins with the preliminary inquiry stage, followed by the formal investigation phase, and subsequently advances to the prosecutorial stage.